Effect Specific Cooling Times on Motility and Membrane Integrity of Cauda Epididymal Bovine Bull Sperm - Asmaa Sh. Aliawy (Journal of Global Pharma Technology, 2020)
Cauda epididymides (CEs) collected post-mortem could be an important source of genetic material from male for conservation and use for assisted reproductive technologies. In this study, we characterize the epididymal sperm (ES) collected post-mortem from CEs of bull cow raised locally. Testicles (n=30) were sliced off from bull cow post-mortem, placed in a box at ambient temperature and transported to the laboratory within 2 hr. The CEs were detached from the testicle and the tail were sliced longitudinally and dropped into a 50-ml conical tube with 15 ml TRIS citric acid. The ES was collected after 10 min, washed through centrifugation and measured. The Live Epididymal Sperm Cooling Sperm 76.40±0.93, 48 hours 68.94±2.38, initial motility, 72 hours 64.23±2.47, 96 hours 60.62±2.40 and 56.62±2.31 per cent, Membrane integrity with initial motility cooling time had the lowest values compared to the gap in initial motility cooling period and 120 hours cooling time .sperm motility whereas through CASA, For CASA (VAP, VSL, VCL, ALH, WOB, LIN), there were no interactions between different cooling times. In addition, different cooling times (P>0.05) affected sperm motion kinematics, i.e. VAP, VSL, VCL, ALH, WOB and LIN, but these parameters are influenced during the cooling process. With epididymal sperm cry presets, both VSL and VAP values were the highest. Cry retained (VSL: 66.25±2.21μm / s, VAP: 81.42±1.46μm / s) compared with 48 hours (VSL: 59.09±1.52μm / s, VAP: 76.67±1.43μm / s), During the cryopreserved cooling period of 5.29±0.14μm (P